(untitled) (Bangladesh Rice Journal, 2018)
Rice tungro is the most destructive and widespread among virus diseases found in almost all rice growing areas. In susceptible varieties, it causes 100% yield loss under favourable environmental conditions. Control of tungro disease by chemical applications is not effective and eco-friendly. Development of resistant variety against tungro is also difficult, because it is necessary to develop resistance either to the insect vector or to the virus or to the both. Identification of varieties with recovering ability will facilitate farmers to cultivate rice in tungro endemic areas. Bangladesh Rice Research Institute released six upland and eight rainfed lowland rice varieties, which were tested to evaluate their recovering ability against tungro disease. The test varieties including susceptible and resistant checks were artificially inoculated by viruliferous vector (Green leafhopper, Nephotettix virescens) of ten days after seeding in net house condition. Among the tested varieties BR26, BRRI dhan33 and BRRI dhan40 were the most susceptible and showed high infection rate against tungro disease. BRRI dhan37 and BR8 showed the highest recovering ability in rainfed lowland and upland rice, respectively, with the lowest yield reduction compared to the resistant check Kumragoir, which could be used in tungro endemic areas. From these investigations, all the tested varieties expressed distinct tungro disease symptoms after three weeks of inoculation. With the advancement of plant growth, varieties BR8 and BRRI dhan37 recovered from tungro syndrome due to their genetic makeup consisting tolerance potentiality showed better yield, while other varieties like BRRI dhan33 and BRRI dhan40 did not produce any grain yield Bangladesh Rice j. 2017, 21(1): 91-100